HUBUNGAN KEBERFUNGSIAN KELUARGA DAN BODY IMAGE DENGAN KEPERCAYAAN DIRI PADA REMAJA DI SMAN 2 CIKARANG UTARA - Anna Fauziah (2021)
Self-confidence is one of the abilities that must be possessed by teenagers. In adolescents who have self-confidence means that he has confidence in his own abilities. The purpose of this study was to analyze the relationship between family functioning and body image with self-confidence in adolescents at SMAN 2 Cikarang Utara. The questionnaire uses the Family Assessment Device Scale, the Multidimensional Body Self Relation Questionnaire-Apperance Scale and the self-confidence scale developed (Andiyanti, 2016). The research method is Chi-Square with a cross-sectional design and the number of samples is 198 respondents. The results showed that there was no significant relationship between family functioning and self-confidence in adolescents with p = 0.055 (p = > 0.05). There is a significant relationship between body image and self-confidence in adolescents with p = 0.001 (p = < 0.05). Families can provide guidance, knowledge and direction to adolescents so that adolescents can have high self-confidence and adolescents need to love themselves more in order to accept the shortcomings that exist in their bodies.